Pulsating low-mass white dwarfs in the frame of new evolutionary sequences : VI. Thin H-envelope sequences and asteroseismology of ELMV stars revisited - Calcaferro, Leila Magdalena (2018)
Context. Some low-mass white-dwarf (WD) stars with H atmospheres currently being detected in our galaxy, show long-period g(gravity)-mode pulsations, and comprise the class of pulsating WDs called extremely low-mass variable (ELMV) stars. At present, it is generally believed that these stars have thick H envelopes. However, from stellar evolution considerations, the existence of low-mass WDs with thin H envelopes is also possible. Aims. We present a thorough asteroseismological analysis of ELMV stars on the basis of a complete set of fully evolutionary models that represents low-mass He-core WD stars harboring a range of H envelope thicknesses. Although there are currently nine ELMVs, here we only focus on those that exhibit more than three periods and whose periods do not show significant uncertainties. Methods. We considered g-mode adiabatic pulsation periods for low-mass He-core WD models with stellar masses in the range [0.1554–0.4352] M⊙, effective temperatures in the range [6000–10 000] K, and H envelope thicknesses in the interval −5.8 ≲ log(MH/M⋆)≲ −1.7. We explore the effects of employing different H-envelope thicknesses on the adiabatic pulsation properties of low-mass He-core WD models, and perform period-to-period fits to ELMV stars to search for a representative asteroseismological model. Results. We found that the mode-trapping effects of g modes depend sensitively on the value of MH, with the trapping cycle and trapping amplitude larger for thinner H envelopes. We also found that the asymptotic period spacing, ΔΠᵃ, is longer for thinner H envelopes. Finally, we found asteroseismological models (when possible) for the stars under analysis, characterized by canonical (thick) and by thin H envelope. The effective temperature and stellar mass of these models are in agreement with the spectroscopic determinations. Conclusions. The fact that we have found asteroseismological solutions with H envelopes thinner than canonical gives a suggestion of the possible scenario of formation of these stars. Indeed, in the light of our results, some of these stars could have been formed by binary evolution through unstable mass loss.